Dated phylogeny and dispersal history of the butterfly subfamily Nymphalinae (Lepidoptera: Nymphalidae) - Su, Chengyong (Sci Rep, 2017)
The origin and dispersal history of the large butterfly subfamily Nymphalinae are not fully understood, due to internal phylogenetic and time calibration issues. We conducted phylogenetic and dating analyses using mitochondrial and nuclear genes of biogeographically diverse groups of the Nymphalinae in order to resolve some controversial relationships and the paleobiogeographic pattern of the subfamily. Our results support the sister relationship of Vanessa (Tribe Nymphalini) and the Nymphalis-group, and the grouping of the three old-world genera (Rhinopalpa, Kallimoides and Vanessula) within Tribe Victorinini. Molecular dating analyses invoking two additional calibrations under the butterfly-host plant coevolutionary scenarios result in a relatively deeper divergence of the subfamily’s two major clades (Nymphalini and the Kallimoids), compatible with the Cretaceous floral turnover scenario during the so-called Cretaceous Terrestrial Revolution. Phylobiogeographic analyses reveal that the Oriental region is probably the center of early divergences for Nymphalinae after the Cretaceous-Paleogene (K-Pg) mass extinction, followed by repeated dispersals into the rest of the Old World and the New World during various periods beginning in Eocene. The biogeographic history indicates that temperature changes and host-plant diversification may have facilitated the dispersals of this butterfly subfamily, with accelerated global colonization during the middle to late Miocene.